The crystal structure of the double salt dipyridin-1-ium bromide tribromide - Bo Wang; Hongxia Pan; Jun Chen; Yunlu Li; Lizhen Chen; Jianlong Wang (Zeitschrift für Kristallographie - New Crystal Structures)
C10H12Br4N2, orthorhombic, Pbcn (no. 60), a = 13.3150(2) Å, b = 13.8478(2) Å, c = 15.7803(2) Å, V = 2909.63(7) Å3, Z = 8, Rgt(F) = 0.0302, wRref(F2) = 0.0948, T = 220 K.